Corrosion Inhibition of Aluminum Alloy (R408, R613) in Sodium Hydroxide Alkali Medium by Expired Drug of Ketoprofen - Ahmed N. Abd; Noor I. Khaleel (Academic Science Journal)
The deterrent effect of medication molecules that have expired, ketoprofen, on aluminum alloy (R408, R613) corrosion in 0.2 M NaOH solution was investigated using the weight loss approach at (20, 30, 40, and 50 0c). When the inhibitor concentration is increased (25,75,125,175,225,275 ppm), the efficiency of inhibition improves. Adsorption is governed by the Langmuir isotherm model. As a result, the effectiveness of inhibition is dependent. Whether the inhibitor is present or not, the strongest inhibitor had an inhibition efficiency of 84 percent. maximum temperature and concentration.